Pengaruh Edukasi Perpajakan Dan Sosialisasi Digital Untuk Meningkatkan Niat Patuh Pajak Di Kalangan Gen-Z - Efendi, Aidil Noval; Purnawan, Fahry; Sofiana, Shevila Nyssa; Pertiwi, Tami Cahya; Linawati, Linawati (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of tax education and digital socialization on tax compliance intention among young people in the higher education environment. The increasing intensity of digital economic activities requires adequate tax knowledge as well as the effective use of digital media to foster tax compliance from an early stage. This research employs a quantitative approach using a survey method, with data collected through structured questionnaires distributed to respondents who met the research criteria. The data were analyzed using statistical analysis techniques to examine the relationships among the variables under study. The results indicate that tax education plays an important role in shaping tax awareness and attitudes, while digital socialization facilitates access to information and enhances perceived benefits of the tax system. Both variables were found to have a positive contribution to encouraging tax compliance intention. These findings are expected to serve as a basis for formulating tax education and socialization policies that are more adaptive to the characteristics of the younger generation in the digital era.